Vyacheslav Viktorovich Novitsky (to the 60th birthday) - Editorial Article (Bûlleten' Sibirskoj Mediciny, 2006)
Creative biography of the prominent Russian scientist — the rector and the chief of pathophysiology chair of the Siberian State Medical University (Tomsk), honoured scientist of RF, academician of RAMS, professor Vyacheslav Victorovich Novitsky is presented. Main directions of scientific and social activity of the chief of one of the leading scientific schools of home medicine are shown.